2021
DOI: 10.1158/1055-9965.epi-21-1140
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Breast Cancer: An Examination of Modification By Underlying Familial Breast Cancer Risk

Abstract: Background: An increased familial risk of breast cancer may be due to both shared genetics and environment. Women with a breast cancer family history may have a higher prevalence of breast cancer-related gene variants and thus increased susceptibility to environmental exposures. We evaluated whether air pollutant and breast cancer associations varied by familial risk. Methods:Sister Study participants living in the contiguous U.S. at enrollment (2003)(2004)(2005)(2006)(2007)(2008)(2009) (N=48,453), all of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Prior epidemiological studies have established associations between air pollution exposure and increased BC risk, with this relationship modulated by factors such as genetics, ethnicity, diet, and cultural context. Particulate matter components PM10 and PM2.5, in addition to gaseous pollutants like NO2 and SO2, have been linked to heightened BC incidence and mortality, particularly in highly polluted Chinese cities [ 80 , 81 ]. PM2.5, NO2, and traffic-related emissions may act as mammary carcinogens [ 15 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior epidemiological studies have established associations between air pollution exposure and increased BC risk, with this relationship modulated by factors such as genetics, ethnicity, diet, and cultural context. Particulate matter components PM10 and PM2.5, in addition to gaseous pollutants like NO2 and SO2, have been linked to heightened BC incidence and mortality, particularly in highly polluted Chinese cities [ 80 , 81 ]. PM2.5, NO2, and traffic-related emissions may act as mammary carcinogens [ 15 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor exposure to NO 2 is closely associated with lung cancer in females through increased activation of estrogen receptors. A few studies have demonstrated that estrogen receptor activation promoted tumor formation by several genomic and non-genomic pathways ( 52 ). Female lung cancer is closely associated with the activation of estrogen receptor pathway and NO 2 is implicated to activate this pathway ( 53 ).…”
Section: Endocrine Disruptive Effects Of Gaseous Constituents Of Smogmentioning
confidence: 99%
“…Es importante tener en cuenta que personas con mayor grado de antecedentes familiares de cáncer de mama, tienen más probabilidades de tener una expresión reducida de los genes de reparación del ADN, y por tanto, es probable que en estas personas sea más fuerte la asociación entre exposición a sustancias como los HAP y el cáncer de mama [34].…”
Section: Aductos De Hap-adn Y Mutación Específica Del Gen Tp53unclassified